Chapter Domitian Coast. Rehabilitation' outlooks of the Northern coast of Campania - Mazzeo, Giuseppe (Proceedings e report, 2020)
Object of the paper is the Domitian Coast, belonging to the North-West of Campania Region, characterized by contrasting factors. The fertility of the soil and the considerable length of an easily accessible and available coastline are threatened by an indiscriminate exploitation of the ground for anthropogenic uses. The paper analyses the Domitian territory and the issues characterizing this particular area on the basis of three categories of elements. The second part indicates the possible intervention policies set up to redevelop this territory.